Development of a score for assessment of radiologic damage in large-vessel vasculitis (Combined Arteritis Damage Score, CARDS) - Nakagomi, D; Cousins, C; Sznajd, J; Furuta, S; Mohammad, A; Luqmani, R; Jayne, D (Clinical and Experimental Rheumatology, 2017)
Objective Outcome assessment in large-vessel vasculitis (LVV) remains challenging and this impairs patient management and the conduct of clinical studies. Previous proposals for outcome tools have not included imaging. This study aimed to develop an imaging score to quantify damage in LVV and to assess the difference between Takayasu (TAK) and giant cell arteritis (GCA). Methods Ninety-six patients (41 TAK, 55 GCA) were identified from local registries at two University Hospitals in the UK. Radiologic lesions including stenosis, occlusion and aneurysm were evaluated in 25 arterial regions by enhanced computed tomography or magnetic resonance angiography. Lesion correlation with combined damage assessment scores was employed in a multiple regression analysis to define the weight of individual lesions and develop a damage index. Results A numerical damage index was developed: the “Combined Arteritis Damage Score (CARDS)”. The index was derived from a formula: number of regions with mild stenosis × 0.6 + number of regions with moderate to severe stenosis × 1.2 + number with occlusions × 1.6 + number with aneurysms × 0.8 in 25 arterial regions. The median CARDS was higher in TAK than GCA (4.1 and 0.6, interquartile range 1.3–5.7 and 0–3, p<0.001). Conclusion We have developed a damage assessment tool, CARDS, based on imaging in LVV of potential value to clinical studies and patient management. TAK and GCA differ in the radiologic severity of disease.